A conformally adapted all-in-one hydrogel coating: towards robust hemocompatibility and bactericidal activity. Issue 11 (8th March 2021) - Zhang, Fanjun; Hu, Cheng; Yang, Li; Liu, Kunpeng; Ge, Yao; Wei, Yuan; Wang, Jingyu; Luo, Rifang; Wang, Yunbing
Abstract : A conformally adapted all-in-one hydrogel coatings that exhibit both hemocompatibility and bactericidal activity possess the potential for applications in blood-contacting devices. Abstract : Hospital-acquired infections and thrombosis caused by bacteria attached to the device surface, or fibrin crosslinking owing to platelet accumulation/activation, are major healthcare challenges that cause morbidity and mortality. To prevent these, surface coating technologies are considered an efficient tool that can combine hemocompatibility and bactericidal activity. In this study, surface-initiated polymerization was conducted to form an all-in-one hydrogel coating that could adapt to diverse medical devices. Different monomer ratios (acrylamide/acrylic acid) were used to adjust the antimicrobial agent loading capacity. The hydrogel coating obtained by a simple dip-absorbing method showed good hemocompatibility and maintained efficient bactericidal activity. We also explored the loading and release of antimicrobial agents with different molecular sizes, including nano-Ag particles, antibiotics, and antimicrobial peptides. The inhibition zone test and confocal laser scanning microscopy revealed that the hydrogel coating could maintain remarkable antimicrobial and antifouling properties for four weeks. Furthermore, the hydrogel coating decreased the platelet adhesion/activation without risk of hemolysis. The ex vivo blood circulation study confirmed the antithrombotic properties of the hydrogel coating. Such all-in-one hydrogel coatings that maintain high cell viability and exhibit both hemocompatibility and bactericidal activity possess the potential for applications in blood-contacting devices.